Bridging public demand and government goals: a WTP-scenario framework for EV diffusion in Cambodia - Hye-Ryoung Jung; Hun Ki Lee; WonMoo Kim (Transportation Research Interdisciplinary Perspectives)
This study aims to identify effective policy interventions for promoting electric vehicle (EV) adoption in Cambodia to meet its Nationally Determined Contribution (NDC) targets within the constraints of a limited government budget. Conventional scenario analyses often overlook consumer preferences, which play a crucial role in EV adoption. To bridge this gap, we introduce a novel approach that integrates scenario analysis with stated preference surveys, evaluating the impact of both financial and non-financial policy options. Our methodology includes assessing greenhouse gas (GHG) mitigation per unit cost, comparing the total cost of ownership between EVs and internal combustion engine vehicles (ICEVs), estimating the required purchase subsidies using willingness-to-pay (WTP) analysis from 452 Cambodian survey participants, and exploring non-financial alternatives such as EV information dissemination. The findings reveal that consumer preference for EVs increases substantially when EV prices are comparable to ICEVs, underscoring the importance of purchase subsidies. Electrifying 25 % of buses and 30 % of motorcycles proved to be a cost-effective strategy for achieving Cambodia’s NDC target of reducing 390 GgCO2eq by 2030, though this would require a budget up to ten times greater than current government allocations. To address these budgetary challenges, our fixed effects analysis suggests that disseminating information on EV reliability, operation, and maintenance could serve as a lower-cost yet effective alternative to financial incentives. This innovative approach provides practical insights into adapting EV policy for developing countries, facilitating a sustainable transition to eco-friendly transportation.